Construction of Wanmai-Qu solid-state fermentation system with aroma-producing yeast and its growth kinetic - HUANG Zhiguo, ZHANG Qingwen, ZHENG Ruoxin, ZENG Bo, REN Zhiqiang, DENG Jie, XIE Jun (Zhongguo niangzao)
A double-layer tray bioreactor was designed. Using Wanmai (peeled wheat) as the fermentation substrate and different aroma-producing yeasts as strains, the solid-state fermentation system for Wanmai-Qu was established. Meanwhile, the growth kinetics model of yeast was established based on the Logistic model. The results showed that the viable counts of Meyerozyma guilliermondii, Wickerhamyces anomalus, Kluyveromyces marxianus and Hanseniaspora uvarum in Wanmai-Qu were all above 4×109 CFU/g after solid-state fermentation for 26 h. The growth kinetics models of 4 aroma- producing strains of yeast were successfully established (R2>0.96, P<0.001), and the relative error between the fitted values and experimental values of the four models was less than 3%, which could well reflect the growth characteristics of the 4 aroma-producing yeasts on Wanmai.